EFEKTIVITAS PENGELOLAAN DANA DESA DALAM PEMBANGUNAN INFRASTRUKTUR LINGKUNGAN DI DESA BINUANG - Diana, Fina; Asirah, Andi; Renaldi, Renaldi (Universitas Patria Artha, 2025)
This research aims to analyze the effectiveness of Village Fund management in the development of environmental infrastructure in Binuang Village, Libureng District, Bone Regency. The research focus includes transparency, participation and accountability as the main principles of good village financial governance. The approach used is descriptive qualitative through observation, interviews and documentation. Data was obtained from primary sources such as the village head, village secretary and village treasurer, as well as secondary sources in the form of village financial reports for 2020–2022. The research results show that the management of village funds in the construction of facilities and infrastructure in Binuang Village, Libureng District, Bone Regency, can be concluded that development funds are managed well, transparently, accountably and participatively. However, there are disparities in environmental infrastructure development. In 2020, development will only focus on Binuang Hamlet and the construction of drilled wells in Kau-Kaue Hamlet. In 2021, development will be more evenly distributed, but in 2022, development will again be concentrated in Binuang, Lacumpe and Paddusa hamlets. This reflects the management priorities of the village government.